Comparative Efficacy of Foam Roller and Static Stretching for Hamstring Tightness in Taekwondo Athletes - Wangate, Krishika Baban; Bavalekar, Namrata Mahesh; Ajagekar, Mrunal Yashwant; Tukare, Vinayak Annappa (Journal of Neonatal Surgery, 2025)
Background: Hamstring tightness is a common issue among athletes, particularly those engaged in sports requiring high flexibility and dynamic lower-limb movements, such as taekwondo. Reduced hamstring flexibility can limit performance, restrict range of motion (ROM), and increase the risk of musculoskeletal injuries. Various interventions, including static stretching and foam rolling, have been widely used to improve flexibility, but their comparative effectiveness in taekwondo athletes remains unclear. Methodology: A randomized clinical trial was conducted with 44 taekwondo athletes aged 12–18 years who practiced at least three times a week. The participants were randomly assigned to two groups Group A: Foam rolling combined with conventional physiotherapy. Group B: Static stretching combined with conventional physiotherapy. The intervention lasted for four weeks, with three sessions per week. Both groups performed strengthening exercises in addition to their respective interventions. Hamstring flexibility was assessed using the 9090 Straight Leg Raise (SLR) Test and the Active Knee Extension (AKE) Test before and after the intervention. Statistical analysis (paired and unpaired t-tests) was performed to evaluate changes in flexibility within and between groups. Conclusion: Both foam rolling and static stretching significantly improved hamstring flexibility in taekwondo athletes. However, no statistically significant difference was observed between the two groups, indicating that both methods are equally effective in reducing hamstring tightness. Foam rolling may provide additional benefits in muscle recovery, whereas static stretching remains a widely used and effective technique for improving flexibility. These findings suggest that athletes and coaches can integrate either method based on individual preference, accessibility, and training needs